Management of Bosworth Fracture: Case Report - , K. M. Onuoha; , U. I. Obong; , O. M. Oyewumi; , I. J. Owolabi (Archives of Current Research International, 2022)
Introduction: Bosworth fracture is an uncommon fracture that involves the distal fibula associated with a dislocation of the proximal fibula fragment being posterior to the tubercle of the tibia distally. As the proximal fibula fragment becomes entrapped behind the Tibia it subsequently makes it irreducible which then necessitates the correction of this fracture surgically. Making an initial diagnosis of this fracture is quite difficult as it is rare and few data in our setting have been recorded with only a handful of documented cases worldwide. Although attempts have been made to reduce this fracture with closed reduction, the outcomes are generally unfavourable and counterproductive. Bosworth fracture is well documented in medical literature but often not easily picked at presentation. Case Presentation: This case report evaluates a 19 year old female student who presented with a 2 hours history of pain and deformity to her right ankle after she had accidentally externally rotated her ankle with the foot in a prone position while running down the stairs. Examination revealed a deformed and swollen right ankle joint, overlying skin was intact, tender limitation of joint movement. She had a failed closed reduction and was subsequently counselled for open reduction and internal fixation with plates and screws.